Estimation of Power Transformer Loading Based on Population Growth: A Case Study in Kulon Progo Regency - Ardiyanto, Yudhi; Suripto, Slamet; Mujaahid, Faaris; Anshori, Rohman Try; Jusman, Yessi; Arkan, Fardhan (Universitas Muhammadiyah Yogyakarta, 2019)
Along with technological advances, it is estimated that the gross regional domestic product (GRDP) of Kulon Progo Regency increases annually by 7.6%, and the population growth of Kulon Progo regency increases annually by 0.9%. However, after assuming with Muara Bungo Regency as a reference to GRDP growth and Population of Kulon Progo Regency due to the influence of the Establishment of New Yogyakarta International Airport (NYIA) in 2019, the population growth every year is 15.78%. While GRDP in 2018 until 2019 equals to 82.91% and next year equals to 7.6 %. Load forecasting the burden for the next ten years by using multiple linear regression affected by NYIA in 2019, the loading of the 150 kV Wates substation is only up to 2021 for the power transformer I of 24.83 MW and the power transformer II 55.40 MW. So it is estimated that for 2022, power transformer I and power transformer II of 150 kV Wates Substation are no longer able to serve the loading. Then, in 2021 a feeder shift and uprating power transformer I need to be conducted. In 2024 a power transformer III is needed. In that year the feed formation from power transformer I and power transformer II was changed to power transformer III.